Measurement of the Charm-Mixing Parameter yCP; Physical Review Letters; Vol. 122, iss. 1 - Aaij R. Roel; Beteta C. A. Carlos Abellan; Adeva B. Bernardo; Eydelman S. I. Semen Isaakovich; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich (2019, 2019)
Title screen